2019
DOI: 10.12688/wellcomeopenres.14909.2
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Human Malaria Infection in Semi-Immune Kenyan Adults (CHMI-SIKA): a study protocol to investigate in vivo Plasmodium falciparum malaria parasite growth in the context of pre-existing immunity

Abstract: Malaria remains a major public health burden despite approval for implementation of a partially effective pre-erythrocytic malaria vaccine. There is an urgent need to accelerate development of a more effective multi-stage vaccine. Adults in malaria endemic areas may have substantial immunity provided by responses to the blood stages of malaria parasites, but field trials conducted on several blood-stage vaccines have not shown high levels of efficacy.  We will use the controlled human malaria infection (CHMI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 57 publications
0
49
0
Order By: Relevance
“…For instance, in malaria, the primary targets for malarial vaccines are children and young infants whereas CHMI studies are carried out in healthy adults. Similarly, historically most challenge studies, have enrolled participants who have no prior history of exposure to challenge agent, however that is changing with more such studies being carried out in endemic regions and allowing for selection of participants who have had pre-exposure [ 24 ]. The route of infection, the dose of the challenge agent use might not appropriately mimic the natural course of infection and hence this might affect the interpretations drawn from such studies [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in malaria, the primary targets for malarial vaccines are children and young infants whereas CHMI studies are carried out in healthy adults. Similarly, historically most challenge studies, have enrolled participants who have no prior history of exposure to challenge agent, however that is changing with more such studies being carried out in endemic regions and allowing for selection of participants who have had pre-exposure [ 24 ]. The route of infection, the dose of the challenge agent use might not appropriately mimic the natural course of infection and hence this might affect the interpretations drawn from such studies [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has allowed the CHMI models to be more widely used, including in endemic regions in Africa [ 23 ]. Conducting CHMI studies in endemic settings can help understand the effects of pre-exposure and immunity which is not feasible in non-endemic settings [ 24 ].…”
Section: Chim Studies and Their Use In Vaccine Developmentmentioning
confidence: 99%
“…Infection control measures at the facility further contain the pathogen thus preventing and protecting third parties from getting unwanted infections. Similar to requirements reported from Kenya [18], facilities need to cater to more than medical concerns to include comfort, entertainment, family visitations (if possible), and provision to meet pressing worldly obligations such as examinations and funerals. These provisions bring with them considerations of measures that protect participants from infections carried by visitors and the visitors, infection from the facility [6].…”
Section: Discussionmentioning
confidence: 99%
“…The Kenyan study was conducted in Nairobi, a non-endemic part of the country and the investigators found it difficult to recruit as many semi-and/or highly-immune individuals as they had planned, largely because of a lack of exposure to prior infection in the local population in Nairobi (the research group have since begun conducting HCS in and/or recruiting from more endemic parts of Kenya (Kapulu et al 2018)). In contrast, the Tanzanian and Gabonese studies took place in endemic areas and were able to recruit semi-immune individuals (and/or those with innate resistance to malaria) more easily.…”
Section: Recruitment Participant Selection Consent and Paymentmentioning
confidence: 99%